PERFORMA PENGGUNAAN KESANTUNAN KOMUNIKASI GUBERNUR DAN WAKIL GUBERNUR SUMATERA BARAT DI DALAM MEDIA SOSIAL - Astya, Alkhadri; Juita, Novia; Ngusman, Ngusman (Universitas Negeri Padang, 2018)
This study aims to describe the performance of the use of communication politeness in terms of the use of the principle of language politeness by the Governor and Vice Governor of West Sumatra in Facebook. This research is a qualitative research using descriptive method. The data in this study are writings written by the Governor and Vice Governor of West Sumatra. Data were collected in the following manner, (1) to capture the screen of the writings of the Governor and Deputy Governor of West Sumatra (period 2016-2021) on Facebook account; (2) transcribes the entire Facebook post; and (3) to observe and determine data that includes the performance of Indonesian politeness. The examination of data validation in this study uses a detailed description technique. After the data collected, then analyzed with the following steps, (1) identifying and transcribing data, (2) classifying, (3) calculating, (4) interpreting data, and (5) summing up data. The conclusion of this study is the performance of Indonesian politeness in the writings in the Governor and Vice Governor of West Sumatra very well. This statement is evidenced by the corresponding speech language utterance of 519 sentences (98%) and non-corresponding nine sentences (2%). Conformity of the use of the principle of communication politeness that many found is the maxim of conclusions and incompatibility of the use of the principle of communication civility that many found is the maxim of praise and humility.Keywords: politeness, governor and deputy governor, facebook